Estimation of Policy Preference Functions: An Application to U.S. Beef Import Quotas - Rausser, Gordon C.; Freebairn, J. W. (The Review of Economics and Statistics, 1974)
Gordon C. Rausser, J. W. Freebairn, Estimation of Policy Preference Functions: An Application to U.S. Beef Import Quotas, The Review of Economics and Statistics, Vol. 56, No. 4 (Nov., 1974), pp. 437-449